A reasonably constructed fluorescent chemosensor based on the dicyanoisophorone skeleton for the discriminative sensing of Fe3+ and Hg2+ as well as imaging in HeLa cells and zebrafish. Issue 20 (25th April 2022) - Zhang, Chuqi; Lv, Xinyan; Liu, Xiuhong; Chen, Hongyun; He, Haifeng
Abstract : A new fluorescent sensor dicyanoisophorone rhodanine-3-acetic acid has been developed by employing a DCI-based push–pull dye as the fluorophore and RDA as the recognition moiety for the simultaneous sensing of Fe 3+ and Hg 2+ . Abstract : In this study, a new fluorescent sensor dicyanoisophorone Rhodanine-3-acetic acid (DCI-RDA) (DCI-RDA) has been developed by employing a DCI-based push–pull dye as the fluorophore and RDA as the recognition moiety for the simultaneous sensing of Fe 3+ and Hg 2+ with a large Stokes Shift (162 nm), high selectivity and sensitivity, and low LOD (1.468 μM for Fe 3+ and 0.305 μM for Hg 2+ ). In particular, DCI-RDA has a short response time (30 s). The Job's plot method in combination with 1 H NMR titration and theoretical calculations was used to determine the stoichiometry of both DCI-RDA-Fe 3+ /Hg 2+ complexes to be 1 : 1. Moreover, DCI-RDA is applied as a fluorescent probe for imaging in HeLa cells and zebrafish, indicating that it can be potentially applied for Fe 3+ /Hg 2+ sensing in the field of biology.